2018
DOI: 10.1017/s0007114518000910
|View full text |Cite
|
Sign up to set email alerts
|

Prospective association between adherence to dietary recommendations and incident depressive symptoms in the French NutriNet-Santé cohort

Abstract: A posteriori healthier dietary patterns and several nutrients have been associated with lower risks of depression in various studies; however, evidence is lacking with regard to the prospective association between adherence to nutritional recommendations (food-based and nutrient-based recommendations) and incident depression or depressive symptoms. In this study, we investigate such associations in the NutriNet Santé cohort. The study sample included 26 225 participants (aged 18-86 years) who were initially fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 49 publications
0
21
2
Order By: Relevance
“…High adherence to dietary recommendations was in several studies showing a significant protective effect against depression and depressive symptoms, and studied in different populations based on origin, age, and gender [19,21,[24][25][26]30,31,36]. High adherence to dietary advice was associated with a significantly reduced risk of developing depressive symptoms in first-time mothers in Australia [30].…”
Section: Adherence To Dietary Recommendations and Risk Of Depressionmentioning
confidence: 99%
See 3 more Smart Citations
“…High adherence to dietary recommendations was in several studies showing a significant protective effect against depression and depressive symptoms, and studied in different populations based on origin, age, and gender [19,21,[24][25][26]30,31,36]. High adherence to dietary advice was associated with a significantly reduced risk of developing depressive symptoms in first-time mothers in Australia [30].…”
Section: Adherence To Dietary Recommendations and Risk Of Depressionmentioning
confidence: 99%
“…High adherence to dietary recommendations was associated with a lower risk of depressive symptoms in adults in France. The adherence was measured regarding four scores namely; modified French Programme National Nutrition Sante'-Guideline Score (mPNNS-GS), Probability of Adequate Nutrient Intake Dietary Score (PANDiet), Diet Quality Index-International (DQI-I), and Alternative Healthy Eating Index-2010 (AHEI-2010) [19]. Risk reduction was in this study estimated to be 21%, 20%, and 12%, respectively, and in the AHEI-2010 group no significance was detected.…”
Section: Adherence To Dietary Recommendations and Risk Of Depressionmentioning
confidence: 99%
See 2 more Smart Citations
“…Large-scale epidemiological studies have consistently documented an association between a healthy diet or dietary indexes reflecting the holistic quality of the diet and a lower risk of depression [47]. For instance, in the NutriNet-Santé study, we have observed that several dietary indexes reflecting nutritional recommendations were prospectively and inversely associated with the risk to develop depressive symptoms [8]. On the opposite, a western dietary pattern or pro-inflammatory diet characterized among other things by more processed foods has been associated with poor mental health [5, 6, 9].…”
Section: Introductionmentioning
confidence: 99%